Assessment of genetic variability, correlation and path analysis for yield and its components in groundnut (Arachis hypogaea L.): GENETIC VARIABILITY FOR YIELD AND ITS COMPONENTS IN GROUNDNUT - MUKESH CHOUDHARY; S P SHARMA; ABHAY DASHORA; S R MALOO (Journal of Oilseeds Research, 2013)
Genetic variability, heritability, correlation and path analysis were carried out in 27 groundnut genotypes. Analysis of variance revealed significant differences among the genotypesfor all the characters. The estimated PCV and GCV indicated existence of fairly high degree of variability for dry pod yield/plant, kernel yield/plant, number of branches/plant, number of mature pods /plant and seed protein content. In corollary to high heritability, estimates of genetic advance as per cent of mean was also observed for dry pod yield/plant, kernel yield/plant, number of mature pods/plant and seed protein content indicating predominance of additive gene effects for these traits. The association study among characters revealed that dry pod yield was positively and significantly correlated with number of pegs/plant, number of mature pods/plant and kernel yield/plant. Path coefficient analysis revealed that kernel yield/plant, biological yield/plant and harvest index had maximum positive direct effect on dry pod yield/plant. The study shows that greater emphasis should be given on these characters while selecting for higher yield and related traits in groundnut.